2011
DOI: 10.4102/sajip.v37i2.879
|View full text |Cite
|
Sign up to set email alerts
|

Workplace bullying: A perspective from the Job Demands-Resources model

Abstract: <strong>Orientation:</strong> Workplace bullying is characterised as a counterproductive interpersonal behaviour, yielding severe consequences for both the individual and the organisation. The occurrence of workplace bullying is often attributed to a stressful work environment.<p><strong>Research purpose:</strong> The purpose of the study was to test the work environment hypothesis by applying the Job Demands-Resources model to workplace bullying. We expected job demands and job r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 68 publications
4
45
0
Order By: Relevance
“…This research indicates that stress activates workplace bullying especially when combined with undesirable personality traits and that essentially deviant behavior correlates more strongly with stress than with personality. Furthermore, Van den Broeck et al (2011)) performed a large study and derived that ''demanding work contexts as well as lack of job resources may make workers vulnerable to becoming a target of workplace bullying''. Moreover, even in the event where high job resources are present, work demands still had a greater impact to victims' reports workplace bullying.…”
Section: Potential Causes Of Workplace Bullyingmentioning
confidence: 99%
“…This research indicates that stress activates workplace bullying especially when combined with undesirable personality traits and that essentially deviant behavior correlates more strongly with stress than with personality. Furthermore, Van den Broeck et al (2011)) performed a large study and derived that ''demanding work contexts as well as lack of job resources may make workers vulnerable to becoming a target of workplace bullying''. Moreover, even in the event where high job resources are present, work demands still had a greater impact to victims' reports workplace bullying.…”
Section: Potential Causes Of Workplace Bullyingmentioning
confidence: 99%
“…From the perspective of the bullies, De Cuyper, Baillien and De Witte's (2009) study additionally found that the relationship between WPB and job security was stronger when perpetrators were highly employable, suggesting that perpetrators are more likely to bully if they are able to get another position more easily. Van den Broeck et al (2011) argue that powerful employees, who have access to job resources, may become bullies. Hauge et al (2009) found that individuals who are exposed to bullying have a significant predisposition to engage as perpetrators of WPB.…”
Section: The Perpetrators Of Wpb: a Review Of The Literaturementioning
confidence: 99%
“…They consequently lack "an empathic inhibitor of aggressive behaviour". A study by Van den Broeck et al (2011) showed that conflict in the workplace may escalate due to job demands and the availability of job resources. From the perspective of the bullies, De Cuyper, Baillien and De Witte's (2009) study additionally found that the relationship between WPB and job security was stronger when perpetrators were highly employable, suggesting that perpetrators are more likely to bully if they are able to get another position more easily.…”
Section: The Perpetrators Of Wpb: a Review Of The Literaturementioning
confidence: 99%
See 2 more Smart Citations